Pemanfaatan Hyperlink untuk Multimedia Presentasi pada Pembelajaran Teks Anekdot - Charlina, Charlina; Rasdana, Oki (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2022)
This study aimed to provide an alternative multimedia option for learning anecdotal texts that are easy and cheap for teachers and interesting and memorable for students. Teachers get many choices in multimedia learning media, which are certainly the most in-demand by students in schools. This case is especially for learning anecdotal texts that have not yet developed. The research method used the development of Rusman, Dedi, and Cepi Microsoft PowerPoint. Researchers used observational data collection techniques, interviews, and documentation. The spiral techniques were employed to analyze the data. The validation results from 3 experts consisting of lecturers, teachers, and computer experts were obtained by 82% and 39 students by 84%. These results indicate that the product is feasible after development.